A label-free fluorescence assay for hydrogen peroxide and glucose based on the bifunctional MIL-53(Fe) nanozyme. Issue 14 (30th January 2018) - Lin, Tianran; Qin, Yuemei; Huang, Yuanlin; Yang, Ruitao; Hou, Li; Ye, Fanggui; Zhao, Shulin
Abstract : A turn-on fluorescent sensor of hydrogen peroxide and glucose was developed based on a label-free nanozyme MIL-53(Fe) without other chromogenic reagents. Abstract : A label-free nanozyme MIL-53(Fe) with the dual-function of catalyzing and emitting fluorescence was utilized for turn-on fluorescence detection of hydrogen peroxide and glucose. The proposed strategy provides a cost-effective, safe and sensitive method for the design and development of multiple enzyme cascade assays for various biomolecules.